Fermented dairy products intake and stroke risk: analyses of NHANES 2007–2018 data - Ma, Sijia; Miao, Yongyue; Wu, Xian (Frontiers in Nutrition, 2025)
BackgroundStroke ranks among the main diseases resulting in death and disability, imposing a heavy burden on both the country and individuals. Healthy foods can effectively prevent the occurrence of stroke, and fermented dairy products are among them. However, in previous studies, the correlation between stroke and fermented dairy products remains controversial.MethodsThe intake of fermented dairy products and the identification of stroke both originated from the data of the NHANES database from 2007 to 2018. This study used a weighted regression model to analyze the association between the total intake of fermented dairy products and the intake of various types of fermented dairy products (yogurt, cheese and buttermilk) and stroke, and conducted subgroup analyses and interaction tests.ResultsThis study included 27,487 American adults, of whom 2.9% had suffered from a stroke. The results of regression analysis indicated that total intake of fermented dairy products and yogurt intake were negatively correlated with stroke. For total intake, after adjusting for all confounding variables, the results revealed that every 50 g rise in intake led to a 7% decline in the stroke risk (OR = 0.93, 95% CI: 0.88–1.00). Meanwhile, when compared to participants having no consumption of fermented dairy products, those with a low intake had a 21% lower probability of stroke (OR = 0.79, 95% CI: 0.66–0.95). Subgroup analysis showed that smoking interacted with stroke and fermented dairy products (p = 0.047). For yogurt, after adjusting for all confounding variables, the results indicated that for every 50 g rise in intake, the probability of stroke declined by 7% (OR = 0.93, 95% CI: 0.86–1.00). However, only high intake of yogurt was associated with a protective effect against stroke, and this relationship remained stable across three models (Model I: OR = 0.49, 95% CI: 0.33–0.75; Model II: OR = 0.50, 95% CI: 0.33–0.75; Model III: OR = 0.62, 95% CI: 0.40–0.96). In contrast, no significant associations were found between cheese and buttermilk intake and stroke risk.ConclusionThis study discovered that, among American adults, the total quantity of fermented dairy products as well as yogurt had an inverse correlation with the risk of stroke, while this correlation did not exist for cheese or buttermilk.